2007
DOI: 10.1111/j.1744-7917.2007.00163.x
|View full text |Cite
|
Sign up to set email alerts
|

Biology and damage traits of emerald ash borer (Agrilus planipennis Fairmaire) in China

Abstract: Emerald ash borer (Agrilus planipennis Fairmaire) (Coleoptera: Buprestidae) is a major stem borer of ash (Fraxinus spp.). It is univoltine in Tianjin, while it is semivoltine in Heilongjiang Province, and both univoltine and semivoltine in Changchun, Jilin Province, where the majority is univoltine. The longevity of emerald ash borer adults is 17.2 ± 4.6 days (n= 45), eggs 9.0 ± 1.1 days (n= 103), univoltine larvae 308 days, semivoltine larvae 673 days, and pupae 61.2±1.6 days (n= 45). It takes about 100 days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
94
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(102 citation statements)
references
References 1 publication
4
94
0
4
Order By: Relevance
“…In the province of Tianjin, China, situated next to the Yellow Sea coast, oviposition has been observed from early May to late June or early July (Wei et al, 2007;Wang et al, 2010). In Heilongjiang province, situated in the northern part of the country, oviposition has been observed from early June until early July (Wei et al, 2007). Oviposition usually takes place under bark flaps or in vertical slits on the trunk.…”
Section: Eggsmentioning
confidence: 99%
See 4 more Smart Citations
“…In the province of Tianjin, China, situated next to the Yellow Sea coast, oviposition has been observed from early May to late June or early July (Wei et al, 2007;Wang et al, 2010). In Heilongjiang province, situated in the northern part of the country, oviposition has been observed from early June until early July (Wei et al, 2007). Oviposition usually takes place under bark flaps or in vertical slits on the trunk.…”
Section: Eggsmentioning
confidence: 99%
“…It has been observed that low density populations on vigorous ash trees tend to support a two year life cycle while stressed trees with higher beetle population densities tend to support a one year life cycle (Cappaert et al, 2005). Wei et al (2007) established a relationship between the duration of the frost free period in three provinces of China and the duration of the life cycle. It takes at least 150 frost free days (with minimum temperatures above zero degrees Celsius) for EAB to complete one generation.…”
Section: Life Cyclementioning
confidence: 99%
See 3 more Smart Citations